2018
DOI: 10.3390/toxins10100390
|View full text |Cite
|
Sign up to set email alerts
|

C-Type Lectin-20 Interacts with ALP1 Receptor to Reduce Cry Toxicity in Aedes aegypti

Abstract: Aedes aegypti is a crucial vector for human diseases, such as yellow fever, dengue, chikungunya, and Zika viruses. Today, a major challenge throughout the globe is the insufficient availability of antiviral drugs and vaccines against arboviruses, and toxins produced by Bacillus thuringiensis (Bt) are still used as biological agents for mosquito control. The use of Cry toxins to kill insects mainly depends on the interaction between Cry toxins and important toxin receptors, such as alkaline phosphatase (ALP). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 53 publications
0
24
0
Order By: Relevance
“…The susceptibility to Bti Cry4Ba and Cry11Aa toxins was determined for different Ae. aegypti strains as described [ 25 ]. At least 5 gradient concentrations of purified Cry4Ba and Cry11Aa protoxins were added to 20 mL filtered water containing 25 early fourth instar larvae and mixed fully.…”
Section: Methodsmentioning
confidence: 99%
“…The susceptibility to Bti Cry4Ba and Cry11Aa toxins was determined for different Ae. aegypti strains as described [ 25 ]. At least 5 gradient concentrations of purified Cry4Ba and Cry11Aa protoxins were added to 20 mL filtered water containing 25 early fourth instar larvae and mixed fully.…”
Section: Methodsmentioning
confidence: 99%
“…At the same time, the membrane with Cry11Aa was also incubated by biotinylated ABP (4 ng/ml), following probed by the primary rabbit polyclonal antibody (1:3000) to biotin and the secondary goat-anti-rabbit-AP-conjugated polyclonal antibody (1:3000). A BCIP/NBT alkaline phosphatase assay kit was used to visualize the binding protein following the manufacturer’s instructions [23].…”
Section: Methodsmentioning
confidence: 99%
“…C-type lectin-20 was also found to interact with ALP1 to reduce Cry toxicity in Ae. aegypti [23]. Resistance can also be induced by the mutation of ATP-binding cassette (ABC) transporter in Heliothis virescens [2428].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the interaction between Cry toxin and toxin receptors from the host midgut brush border membrane vesicles (BBMVs) is the initial step in the insecticidal activity of the Cry protein toxins [ 107 , 108 , 109 , 110 ]. Several researchers also showed the interaction between midgut immune-related proteins and Cry toxin [ 111 , 112 , 113 ]. There is evidence showing that immune-related protein like Dorsal and peroxidase C in the midgut juice of P. xylostella and S. exigua can bind to the Cry1Ab1 protein toxin [ 111 ].…”
Section: The Host Immune System In Response To Bt Infectionmentioning
confidence: 99%
“…Similarly, it has been reported that C-type lectin-20 (CTL-20) in Aesdes aegyptii has the potential to bind to both toxin receptors and Cry toxins to affect the interactions between Cry toxins and toxin receptors to reduce Cry toxicity in Aedes aegypti [ 112 ]. Similarly, another study on immune-related peptidoglycan recognition protein (PGRP) gene expression and PO activities in Cry1Ac-susceptible and -resistant P. xylostella found that the resistant strain of P. xylostella had higher PO activity compared with the susceptible strain [ 114 ].…”
Section: The Host Immune System In Response To Bt Infectionmentioning
confidence: 99%